The Effect Of Local Taxes And Local Levies On The Original Revenue Of South Nias Regency In 2022–2024 - Andalkris Yuliasih Laia; Junawan Junawan; Irawan Irawan (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the effect of regional taxes and levies on local revenue (PAD) in South Nias Regency in the 2022–2024 fiscal year. Regional taxes and levies are two main components that contribute directly to increasing PAD, which ultimately serves as an indicator of the fiscal independence of local governments. This study uses a quantitative approach with multiple linear regression analysis to determine the relationship between the independent variables (regional taxes and levies) and the dependent variable (local revenue). The data used are secondary data obtained from the Regional Financial Management Agency (BPKD) of South Nias Regency, APBD realization reports, and other relevant official documents during the study period. The results show that regional taxes have a positive and significant effect on local revenue. Similarly, regional levies have a positive but not always significant effect on increasing PAD. Simultaneously, regional taxes and levies together contribute significantly to the PAD of South Nias Regency. These findings indicate that optimizing local tax collection and improving the quality of public services related to levies need to be a focus of local governments to increase financial independence and budget management efficiency.